Gestão democrática para a acessibilização de programas de Pós-Graduação Stricto Sensu: o caso UFSCar - Lima, André Henrique de (2023)
This research discusses the democratic management dedicated to the promotion of accessibility in contexts of postgraduate programs - PPGs. In recent years, the democratization of these spaces has culminated in the expansion of the representation of human diversity. Thus, among other challenges, PPGs have been urged to recognize and ensure the rights of people with disabilities at the time of entry (formal right), access (material right), permanence, and title. In this context, the present research had the general objective of identifying and analyzing factors that constitute the legitimation of the right of entry, access, permanence, and title of people with disabilities in stricto sensu graduate programs. As specific objectives, we have: a) to understand and systematize the offers and demands that people with disabilities present to institutional managers involved in PPGs; b) identify elements that support institutional guidelines for the promotion of accessibility in postgraduate contexts, and; c) approach the Institutional Analysis approach to the elements that indicate and configure the construction of accessibility in PPGs. In compliance with ethical principles in research, we carried out an exploratory and qualitative case study. Data collection took place at the Federal University of São Carlos - UFSCar, in the online modality, and had the participation of eight PPG coordinators (in ten brainstorm sessions) and two Pro-Rectory of Graduate Studies managers - ProPG (in three institutional meetings). The data were treated in light of the approach of content analysis and its analysis was based on the compendia of the theory of Institutional Analysis by Gregório Baremblitt. The results suggest that democratic management for accessibility depends on the co-responsibility of the actors involved, orchestrated in an interdisciplinary and intersectoral way, having as a guiding principle the materialization of the rights of people with disabilities (among servers and students) within any area of knowledge. In this sense, in addition to the dialogue established with the academic-scientific community, the research results bring some subsidies to improve debates and guidelines for implementing policies and practices of democratic management to promote accessibility.